Matrix metalloproteinases in the cervical mucus plug in relation to gestational age, plug compartment, and preterm labor - Danielsen Carl C; Hein Merete; Becher Naja; Uldbjerg Niels (BMC, 2010)
Abstract Background High concentrations of matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) have been identified in the cervical mucus plug (CMP) at term of pregnancy. Their physiological and pathophysiological implications, however, remain to be elucidated, and CMPs from preterm labor have never been examined. This study was therefore conducted to describe the concentrations of MMP-2, TIMP-1, MMP-8 and MMP-9 in the CMP in relation to gestational age, IL-8 as an indicator of inflammation, compartment of the CMP, and preterm labor. Methods An aliquot of the distal plug compartment facing the vaginal microflora (CMP-dist) was collected from non-pregnant (n = 15), early pregnant (n = 15) and term pregnant women (n = 15). Whole CMPs shed during active vaginal term (n = 15) and preterm (n = 4) labor were also included. Protein concentrations were determined by enzyme-linked immunosorbent assay (ELISA). Results MMP-2 was not detectable in the non-pregnant CMP-dists whereas high concentrations were found in early pregnancy followed by an 85% decline at term. High concentrations of TIMP-1 were found in both the non-pregnant and early pregnant CMP-dists with a 90% decline at term. Consequently, the molar TIMP/MMP ratio was 40 in the non-pregnant state and 0.2 at term. The MMP-2 and TIMP-1 concentrations were alike in the CMP-dists and the whole CMPs. MMP-8, MMP-9, and IL-8 were mainly found in the distal CMP compartment. MMP-8 and MMP-9 concentrations were several fold increased in this compartment during pregnancy compared to the non-pregnant state. In the preterm whole CMPs, MMP-8, MMP-9 and IL-8 were 2 to 5 fold increased compared to term whole CMPs. Conclusions These results suggest that CMP MMP-2 reflects the non-leukocyte dependent cervical remodeling that occurs in early pregnancy, whereas MMP-8 and MMP-9 are involved in the defense against ascending infections primarily located to the distal compartment of the CMP. The upregulation of MMP-8, MMP-9 and IL-8 in whole CMPs from preterm labor may indicate the involvement of an intrauterine infection.